2-kW-level superfluorescent fiber source with flexible wavelength and linewidth tunable characteristics. (1st October 2021) - Ye, Jun; Fan, Chenchen; Xu, Jiangming; Xiao, Hu; Leng, Jinyong; Zhou, Pu
Abstract: The superfluorescent fiber source (SFS) with tunable optical spectrum has shown great application potential in the sensing, imaging, and spectral combination. Here, we demonstrate for the first time a 2-kW-level wavelength and linewidth tunable SFS. Based on a flexible filtered SFS seed and three stages of fiber amplifiers, the output power can be scaled from the milliwatt level to about 2 kW, with a wavelength tuning range of 1068–1092 nm and a linewidth tuning range of 2.5–9.7 nm. Moreover, a numerical simulation is conducted based on the generalized nonlinear Schrödinger equation, and the results reveal that the wavelength tuning range is limited by the decrease of seed power and the growth of amplified spontaneous emission, whereas the linewidth tuning range is determined by the gain competition and nonlinear Kerr effects. The developed wavelength and linewidth tunable SFS may be applied to scientific research and industrial processing.